Describing the city, describing the state : representations of Venice and the Venetian Terraferma in the Renaissance - Toffolo, Sandra (Studies in medieval and Reformation traditions, 2020)
"'In Describing the City, Describing the State' Sandra Toffolo presents a comprehensive analysis of descriptions of the city of Venice and the Venetian Terraferma in the Renaissance, when the Venetian mainland state was being created. Focusing on an extensive variety of descriptions, the book demonstrates that no one narrative of Venice prevailed in the early modern European imagination, and that authors continuously adapted geographical descriptions to changing political circumstances. In doing so, it shows the importance of studying geographical representation and early modern state formation together. Moreover, it challenges the long-standing concept of the myth of Venice, by showing that Renaissance observers never saw the city of Venice and the Venetian Terraferma in a monolithic way"--